Diarrhoea in neonatal small ruminants: Updated review and proposed measures for its control in Greece. - KRITAS (Σ.Κ. ΚΡΗΤΑΣ), S. K.; KARATZIAS (Χ. ΚΑΡΑΤΖΙΑΣ), H.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ), C.; KYRIAKIS (Σ.Κ. ΚΥΡΙΑΚΗΣ), S. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
Diarrhoea in neonatal small ruminants appears to be responsible for substantial financial losses in sheep and goat enterprises worldwide, including Greece. Enterotoxigenic strains of Escherichia coli, Clostridium perfringens type B, rotavirus, Coronavirus, Cryptosporidium spp, and Eimeria spp. are the main causes of scour problems in neonatal lambs and kids up to the age of 3-4 weeks. In this study, a review of the causative agents, their pathogenesis, and clinical and autopsy findings possibly helpful for diagnosis is attempted. Moreover, appropriate therapeutic and preventive measures for effective control of diarhoea, and measures for controlling the speading of the causative agents among sheep and goat farms, are suggested.